Students Perceptions Towards Public Speaking Class to Develop Oral Communication Skill - Novi Rizki Amelia; Alya Mahastra Putri; Asyfi Hidayat UsyaBani; Shafartine Isnista Millendiani Putri (Journal of Applied Linguistics (ALTICS), 2024)
The purpose of this study is to find out the students' perception regarding the Public Speaking Class to improve their oral communication at English Education Department’s students 2020-2022 in Universitas Perjuangan Tasikmalaya. The researcher applied the Descriptive Qualitative Method to conduct this study since it would be possible to collect the data of the students’ perception by giving the questionnaires as the way to collect the data. The sample of this research consisted of 51 students. The sample was taken by using Purposive Sampling Technique. Based on findings, it finds that students gave mostly positive perceptions toward implications of Public Speaking Class to develop their oral communication skill.. Those positive responses came from their experience in learning Public Speaking class. From the public speaking class, they got a lot of knowledge about how to deliver a good speech, comprehend the types of speech, and even overcome nervousness in front of an audience. To sum up, they have the perception that public speaking class is a good start for their future careers. Keywords: Student’s Perceptions, Public Speaking Class, Oral Communication.